Hipoterapevtski tim in kompetence - Vukovič, Goran; Werber, Borut; Lambić, Ana; Jerin, Matija; Medved, Tilen; Breznikar, Tilen; Polner, Nikita; Lauko, Lina; Podobnik, Metka; Šabec , Ana; Cerkovnik , Pia; Ramšak, Špela; et al. (University of Maribor Press, 2020)
Hippotherapy Team and Competencies.Hippotherapy is a form of physiotherapy that involves the use of a horse as a therapeutic tool to effectively treat a patient, where the rhythm of the horse’s walking with its three-dimensional movement constantly promotes the patient’s balance and proper posture. The problem situation arises with the general knowledge and prevalence of hippotherapy in Slovenia. For the needs of the research, we used a combination of research approaches. We started with a critical review of secondary literature sources and used the synthesis method to prepare an overview of the field, which we upgraded with a qualitative approach in which, through interviews and conversations with environmental experts, we developed many models for a comprehensive presentation of hippotherapy, business model, process organization chart, etc.